Statistical optimisation of organic additives for maximum brightness and brightener analysis in a nickel electroplating bath - Ramazan, K.; Esma, S.; Belkıs, U. (Informa UK Limited, 2015)
In this study, a 23 full factorial design of experiment (DOE) method was first employed for statistical modelling and analysis of the results obtained from the use of organic additives, such as propargyl alcohol (PA), butynediol ethoxylate (BEO), and pyridiniumsulphobetaine (PPS), in nickel electroplating. The main and interactive effects on properties of factors PA, BEO, and PPS, were investigated through the model equations designed by two-levell full factorial design (FFD). The results show that PA has the greatest effect on thickness, while BEO and PPS interactions have this on brightness. A mixture of BEO and PPS was optimised to obtain the brightest plating and identified as optimal brightener. The use of cyclic voltammetry to characterise the brightener in a nickel electroplating bath was extended to take into account the effect of other chemicals in the Watts bath. A good correlation was obtained between the concentration change of the brightener in the nickel bath and the current levels.